Job Satisfaction, Job Characteristics, Job Organization, and Social Factors in Manufacturing Industries: A Case Study in Malaysia - Dawal, Siti Zawiah Md (ANIMA Indonesian Psychological Journal, 2008)
The relationship between job satisfaction, job characteristics, job organization and social factors in two automotive industries in Malaysia were analyzed. Surveys were conducted to investi- gate the relationship and a set of multiple choice questionnaires was developed. Male subjects (N = 170) between the ages of 18 to 40 years with a mean age of 26.8 and standard deviation (SD) of 5.3 years and mean work experience of 6.5 and standard deviation (SD) of 4.9 years took part in the sur- vey. Results show that job characteristics, job organization and social factors are significantly related to job satisfaction. Further, it also highlighted the most significant attributes from each main factor that influence the job satisfaction. Telah dianalisis hubungan antara kepuasan kerja, ciri-ciri kerja, organisasi kerja, dan faktor sosial pada dua industri otomotif di Malaysia. Survei dilakukan untuk menyelidiki hubungan tersebut dan telah pula dikembangkan kuesioner pilihan ganda. Subjek pria (N = 170) berusia antara 18 – 40 tahun dengan rerata usia 26.8 dan simpangan baku 5.3 tahun dan rerata pengalaman kerja 6.5 tahun dan simpangan baku 4.9 tahun berpartisipasi dalam survei ini. Hasil menunjukkan bahwa ciri-ciri kerja, organisasi kerja, dan faktor sosial secara bermakna berhubungan dengan kepuasan kerja. Selanjutnya, juga disoroti atribut yang paling bermakna dari tiap faktor utama yang memengaruhi kejenuhan kerja.